5x-3+7x+2=6x+3+6x-4

Simple and best practice solution for 5x-3+7x+2=6x+3+6x-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-3+7x+2=6x+3+6x-4 equation:



5x-3+7x+2=6x+3+6x-4
We move all terms to the left:
5x-3+7x+2-(6x+3+6x-4)=0
We add all the numbers together, and all the variables
5x+7x-(12x-1)-3+2=0
We add all the numbers together, and all the variables
12x-(12x-1)-1=0
We get rid of parentheses
12x-12x+1-1=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0

See similar equations:

| 2y^2+4=92 | | 23-2x=3x-17 | | 36-6x=3x-18 | | –x+4=3x+4 | | 6x+34=8x+11 | | 4x+5/3=3/4 | | 3x-8=3x+23 | | 0.80x+0.10(40)=0.40(46) | | 4x+5/4=11/3 | | 4x+11/3=5/4 | | 280/200=x/1 | | -18=-9(b-2) | | 14+6t=7t+14 | | 4x+11/5=3/4 | | -4(x+2)-4=-12 | | -3b-4b=28 | | 5y-15=2y-27 | | F(x)=2x-16x+9 | | 2=-2(s-5) | | 4x+5/3=11/4 | | 18=16-b/6 | | 3=4+x/2 | | 4p-3=13( | | -1=4+x/6 | | v/5+17=17 | | q/6-10=-9 | | 3k-6=2k-1 | | X/2-8x;x=10 | | -5p+8=53 | | 2=z/6 | | 5x7=2x+23 | | (2x-x)2=225 |

Equations solver categories